The (Un)Resolved Case: Blurry vision, left foot drop and brain cysts. Issue 2 (13th September 2019) - Di Liberto, Giovanni; Aícua-Rapún, Irene; Comps, Jean-Nicolas; Sherif, Mohamed; Boillat-Blanco, Noémie; Brouland, Jean-Philippe; Maeder, Philippe; Daniel, Roy T; Du Pasquier, Renaud A; Sokolov, Arseny A
This clinical vignette describes the interdisciplinary diagnostic approach to a patient with cystic brain lesions. The scope of this case is to develop the clinical reasoning skills of trainees in clinical neuroscience, taking into account alternative diagnoses and unusual clinical presentations.